ผลของโปรแกรมการจัดการตนเองโดยการสนับสนุนจากเพื่อนต่อระดับฮีโมโกลบินที่มีน้ำตาลเกาะของผู้ป่วยโรคเบาหวานชนิดที่ 2 - จิราพร นิลสุ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The Quasi-experimental research was designed to study the effect of peer supported self-management program on HbA1C level in diabetes type 2 patients in Rayong hospital .The concepts of peer support developed by Hiesler (2009) and self management method of AADE (2009) were used as a conceptual framework. The sample were 40 type 2 diabetes patients who have HbA1C > 8% in past 6 months in diabetic clinic of Rayong hospital, 20 per group. The control group received usual care while the experimental group received the peer support self–management program. The intervention, developed by researcher, consisted 5 steps: 1) Assessment, 2) Goal setting, 3) Planning, 4) Implementation, and 5) Evaluation/Follow-up for blood sugar control. The researcher met subjects 3 times and diabetic peers called subjects every two weeks. The intervention was reviewed for content validity by a panel of 5 experts. Lesson plan, slide, and a handbook of Diabetes conquer was developed as part of the intervention. Diabetic knowledge of peer was measured to monitor the intervention. Its content validity index was 0.7, and KR – 20 was 0.85. A test-retest was used to examine the stability of HbA1C report with a correlation coefficient (r) of .99. Data were analyzed using descriptive and t-test statistics. Major finding of this study were as follow: 1.The mean of HbA1C level of type 2 diabetes mellitus patients after receiving the peer support self-management program (x= 9.12± SD 2.06) was significantly lower than before receiving the program (x= 10.40± SD 2.34 ) (t = 3.416, df = 19, p<.01). 2.The reduction of HbA1C level of type 2 diabetes mellitus patients after receiving the peer support self- management (d= 1.83±1.28) was significantly higher than that of the control group (d= 0.01±1.14) (t = 2.63, df = 38, p<.05).